Newspaper article titled 'An Irishman’s Diary' by Niall Kiely [Irish Times] - Kiely, Niall; Irish Times, Ltd. (Dublin, Ireland) (1981)
The newspaper article describes a letter Patricia Sheehan sent to the [Irish Times] regarding a letter of comfort she received from Christy Brown from the time of her husbands death. Niall Kiely explains in the newspaper article that Patricia Sheehan wanted to share Christy's letter as it "shows a facet of his philosophy of life, and his spirituality, that will not be known to many, and may be a comfort to others who are bereaved by the loss of a loved one". The newspaper cutting contains extracts from both Christy Brown's and Patricia Sheehan's letters.
Typescript.
Keywords: Brown, Christy, -- 1932-1981; Sheehan, Patricia, -- 1928-1994 -- Correspondence; Carr, Mary, -- b.1945